Development of Web-Based High School Trigonometry Learning Tools with Problem-Based Learning Models Reviewed from Creative Thinking, Critical Thinking, and Self-Esteem Skills - Hartono Hartono; Meiliza Aminy (Fakultas Ilmu Pendidikan Universitas Muhammadiyah Jakarta, 2026)
Creative thinking, critical thinking, and self-esteem are essential competencies in 21st-century mathematics education; however, their development remains suboptimal. This study aimed to develop a website-based trigonometry learning tool integrating the Problem-Based Learning (PBL) model and to evaluate its validity, practicality, and effectiveness. A Research and Development (R&D) approach using the ADDIE model was employed with 35 tenth-grade students at MAN Batu Bara. The instruments included expert validation sheets, teacher and student response questionnaires, learning implementation observation sheets, creative thinking and critical thinking tests, and a self-esteem questionnaire. Descriptive statistics were used to evaluate validity and practicality, while effectiveness was examined using a one-sample t-test against predetermined performance benchmarks. The results showed that the developed learning tool was highly valid based on expert evaluations and highly practical based on teacher responses, student responses, and learning implementation observations. Students' post-implementation mean scores significantly exceeded the benchmark values (p < 0.05). Moreover, 83% of the students achieved mastery in creative thinking, 71% in critical thinking, and 74% demonstrated very high self-esteem. These findings indicate that the developed learning tool satisfies the criteria of validity, practicality, and effectiveness as an instructional product for trigonometry learning.